Validity of bacterial pneumonia score for predicting bacteremia in children with pneumonia - Rosalia Theodosia Daten Beyeng; Putu Siadi Purniti; Roni Naning (Paediatrica Indonesiana, 2011)
Background Bacteremia in children with pneumonia reflects a severe condition, with longer duration of hospital care and potentially lethal complications. Early detection of bacteremia in patients with pneumonia may reduce serious complications. Few bacteremia screening tools have been widely used in chidren with pneumonia. One of those tools is the bacterial pneumonia score (BPS).Objective To assess the validity of the bacterial pneumonia score for predicting bacteremia in pediatric patients with pneumonia.Methods A diagnostic test was conducted on children aged 1 to 60 months hospitalized with pneumonia from December 2009 to August 2010. Subjects were collected consecutively. Pneumonia was diagnosed using the World Healt Organization (WHO) criteria. Subjects underwent complete blood counts and blood culture examinations at admission. Statistical analyses included sensitivity, specificity, positive and negative predictive value (PPV/NPV), positive and negative likelihood ratio (PLR/NLR), and post-test probability.Results Our study included 229 children. Based on BPS with a cut-off score of â‰¥ 4, the sensitivity was 83.3%, specificity 49.7%, PPV 8.4%, NPV 98.2%, PLR 1.66, NLR 0.31, and post-test probability 8.4% for detecting bacteremia in pediatric pneumonia patients.Conclusion BPS can not be used for predicting bacteremia in pediatric patients with pneumonia.